Portfolio Assessment and Quality Teaching - Kim, Youb; Sensale Yazdian, Lisa (Theory Into Practice, 2014)
Our article focuses on using portfolio assessment to craft quality teaching. Extant research literature on portfolio assessment suggests that the primary purpose of assessment is to serve learning, and portfolio assessments facilitate the process of making linkages among assessment, curriculum, and student learning (Asp, 2000; Bergeron, Wermuth, & Hammar, 1997; Cohen & Wiener, 2003; Neill & Mitchell, 1995; O'Malley & Pierce, 1996; Smith & Ylvisaker, 1993; Yancey, 1996). Because a learning portfolio is a collection of student work samples over time, it provides teachers with opportunities to understand the process of student learning. This is especially important in the current educational context where teachers are expected to teach all students, including English language learners, to develop high-level thinking and content knowledge aligned with Common Core State Standards. To support teachers to provide quality teaching that meets Common Core State Standards for diverse English language learners, we begin our article with 3 important reasons for using portfolio assessment. We then describe procedures for implementing portfolio assessment in individual classrooms.